Pterostilbene antagonizes homocysteine-induced oxidative stress, apoptosis and lipid deposition in vascular endothelial cells - Qiao Jiang; Li Wang; Xu Si; Yuanyuan Bian; Weijia Zhang; Huijun Cui; Hailong Gui; Ye Zhang; Bin Li; Dehong Tan (Food Science and Human Wellness)
Hyperhomocysteinemia (HHcy) causes oxidative stress, induces apoptosis, and leads to damage to the vascular endothelium is the starting point of atherosclerosis. Pterostilbene (Pte) has been reported to have antioxidant and anti-apoptotic effects under various pathological conditions. The purpose of this study was to explore whether Pte can inhibit the oxidative stress and apoptosis of vascular endothelium induced by homocysteine (Hcy) and to explain the possible mechanism by which it occurs. The results showed that 20 μmol/L Pte significantly reduced the accumulation of reactive oxygen species, malondialdehyde, and lipids in cells induced by Hcy and promoted the activities of superoxide dismutase and catalase. The Hoechst 33342/PI staining assay showed that Pte antagonized Hcy-induced apoptosis. Pte inhibited Hcy-induced Akt dephosphorylation, increased p53, and decreased the Bcl-2/Bax ratio and caspase-9/caspase-3 activation in a dose-dependent manner. LY294002 pretreatment partially reversed the protective effect of Pte by blocking the PI3K/Akt pathway. Moreover, Pte reduced lipid deposition in human umbilical vein endothelial cells (HUVECs). This study proposes that Pte can inhibit Hcy-induced oxidative stress and apoptosis of HUVECs, and the PI3K/Akt/p53 signaling pathway of apoptosis was revealed. These results suggest that Pte exhibits significant potential for dealing with HHcy-induced vascular endothelial injury, such as atherosclerosis.